Acupuncture-related adverse events: a systematic review of the Chinese literature - Zhang, Junhua (World Health Organization, 2010)
OBJECTIVE: To systematically review the Chinese-language literature on acupuncture-related adverse events. METHODS: We searched three Chinese databases (the Chinese Biomedical Literature Database, 1980–2009; the Chinese Journal Full-Text Database, 1980–2009; and the Weipu Journal Database, 1989–2009) to identify Chinese-language articles about the safety of traditional needle acupuncture. Case reports, case series, surveys and other observational studies were included if they reported factual data, but review articles, translations and clinical trials were excluded. FINDINGS: The inclusion criteria were met by 115 articles (98 case reports and 17 case series) that in total reported on 479 cases of adverse events after acupuncture. Fourteen patients died. Acupuncture-related adverse events were classified into three categories: traumatic, infectious and “other”. The most frequent adverse events were pneumothorax, fainting, subarachnoid haemorrhage and infection, while the most serious ones were cardiovascular injuries, subarachnoid haemorrhage, pneumothorax and recurrent cerebral haemorrhage. CONCLUSION: Many acupuncture-related adverse events, most of them owing to improper technique, have been described in the published Chinese literature. Efforts should be made to find effective ways of monitoring and minimizing the risks related to acupuncture.